Intravesical Migration of Missed Intrauterine Device Associated with Stone Formation: A Case Report and Review of the Literature - Mücahit Kart; Turgay Gülecen; Murat Üstüner; Seyfettin Çiftçi; Ufuk Yavuz; Cüneyd Özkürkçügil (Case Reports in Urology)
Intrauterine device is the most widely used method of reversible contraception. It may cause various complications including perforation of uterus. In this case, 44-year-old woman was presented with lower urinary tract symptoms after six years of insertion. Patient has no remarkable physical or laboratory finding but abdominal ultrasound revealed a 27 mm hyperechogenicity, suggestive of foreign body or calculus on the posterior bladder wall which was removed endoscopically. This case highlights the need of immediate and periodic evaluation of women with intrauterine device to avoid missing serious complications.